MATHEMATICAL MODELING OF WORK OF THE DIRECTORATE OF RAIL TRAFFIC FLOWS - Kharchenko, O. I. (Science and Transport Progress, 2007)
There is an example of the linear mathematical models construction of the railway traffic management.